Evaluation of the experimental parameters for the morphological tunning of monodispersed calcium hydroxyapatite. Issue 7 (8th June 2021) - Akhtar, Khalida; Pervez, Cynthia
Abstract: The new era of science and technology signifies the control over the size and shape of materials. The size and shape variation plays a crucial role in determining the properties of the material and promises a potential application of these materials. The present study focuses on the fabrication of the most important inorganic biomaterial, namely, calcium hydroxyapatite (Ca10 (PO4 )6 (OH)2 ) (HA) in a nano range having uniform morphology and high surface to volume ratio. HA particles were successfully synthesized by the hydrothermal homogenous precipitation, having whiskers and cubic shaped particle morphology with high crystallinity in size range of 6.1 nm and 9.7 nm, respectively. The morphological features of the particles were further analyzed by Scanning electron microscope (SEM), and the structural evolution was studied by Fourier transform infrared spectroscopy (FT-IR) and X-Ray diffraction analysis (XRD). Urea was used as a precipitating agent to raise pH and promote nucleation & rapid growth of HA crystals at low supersaturation. The effect of different reaction parameters on HA particle morphology was also investigated. Aging time showed a sensitive dependence on the morphological features of HA particles, and the pH of a solution had a vital role in the formation of various crystal phases of calcium phosphate, which served as a precursor in HA formation. Graphical Abstract: